Transient sick sinus syndrome with complete atrioventricular block associated with ergonovine intake: A case report. Issue 44 (November 2017) - Wang, Hui-Ting; Liu, Wen-Hao; Chen, Yung-Lung
Abstract: Rationale: More mature or older women are more likely to undergo in vitro fertilization and embryo implant. These women have a greater chance of receiving ergonovine therapy because of a suspected abortion. We present this case report to call attention to a latent lethal adverse effect in everyday obstetric practice using ergonovine. It requires more attention and close monitoring Patient concerns: We presented the case of a 38-year-old female patient with general weakness and mild chest tightness after ergonovine use. Diagnoses: She was diagnosed as transient sick sinus syndrome and complete atrioventricular block with junctional escape rhythm after diagnostic work up. Interventions: Conservative treatment with discontinuation of ergonovine and bed rest. Outcomes: Her sinus rhythm returned to normal the day after ergonovine was discontinued. The patient remained symptom-free since recovery of her sinus rhythm. Lessons: Ergonovine may cause symptomatic and lethal bradyarrhythmia. Withdrawal of the causative medication and adequate supportive care can lead to a favorable outcome in these patients. More related cases should be reported. Further evaluation for treatment and prognosis are necessary.